PENTINGNYA PENANAMAN MODAL ASING DAN PENGATURANNYA DI INDONESIA - Sigit Irianto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
Arrangements and policies in the field of investment in Indonesia have been experiencing various barriers and developments. Various factors that greatly affect were not merely internal domestic interests, but also the interests of the investor's origin country as well as other international interests. Foreign investment is important because of the limitations imposed by Indonesia in the areas of capital, technology and quality of human resources.Arrangement in the field of investment is very influential for foreign investment. It can be seen from the fluctuation development of foreign investment in Indonesia. Enactment of Law Number 25 Year 2007 concerning Capital Investment is an embodiment to better accommodate the various interests of both domestic and foreign interests. Demands of equal treatment, both in the field of certainty and legal protection for investors (investors), both foreign and domestic investors, have been regulated in the Investment Law. But one thing is for sure, the state shall have the authority and obligation to regulate investment, both foreign and domestic investment to realize the welfare of the people, as mandated by the 1945 Constitution.